Implementation of The Haversine Algorithm and Point of Interest Feature for Patrol Route Optimization - Aryan Fitrah Adillah; Moh. Ali Romli (bit-Tech, 2025)
This study presents the design and implementation of Poliscope, a mobile-based patrol monitoring application developed to address inefficiencies in traditional paper-based security systems. Conventional patrol methods often suffer from fragmented data collection, limited real-time visibility, and poor accountability, reducing operational reliability. The system adopts a client-server architecture, utilizing Flutter for the frontend and Node.js with Express.js and MySQL for the backend to ensure performance and scalability. At the core of the system are two computational features: the Haversine algorithm, applied dynamically to calculate real-time geodesic distances between officers and patrol points with an average spatial accuracy of ±10 meters and the Point of Interest (POI) feature, which enables officers to tag, record, and manage field locations directly during patrols. To assess reliability, Black Box Testing was conducted across critical modules such as authentication, patrol session management, and POI handling. All functional scenarios executed successfully, with an average response time under 1.5 seconds, confirming the system’s responsiveness and operational robustness. The findings indicate that Poliscope significantly enhances patrol oversight through improved spatial accuracy, structured documentation, and real-time monitoring capabilities. Its integration of continuous geospatial tracking and dynamic task verification addresses key gaps in legacy systems. As a result, the application supports faster response times, more accountable field reporting, and enhanced supervisory control, offering a practical and scalable solution for modernizing patrol management in both public and private sector security operations.